Functions and application of glomalin-related soil proteins: a review - Gao, Wei-Qin; Wang, Peng; Wu, Qiang-Sheng (Penerbit Universiti Kebangsaan Malaysia, 2019)
Glomalin that is a kind of glycoprotein produced by arbuscular mycorrhizal fungi in the phylum Glomeromycota, has some characteristics of hydrophobins with insolubility and difficulty in its extraction. The protein is highly homologous with heat shock protein 60. In soils, glomalin is measured as glomalin-related soil protein (GRSP). GRSP is highly positively correlated with soil aggregate stability, because it is a new component of soil organic matter. The mycorrhiza-released glomalin has represented potential functioning in soil ecosystems, which include promoting the storage of soil organic carbon, improving the structure of soil aggregates, enhancing the resistance of plants, and reducing the metal toxicity of plants. In addition, some potted and field experiments have been performed to exogenously apply the GRSP in crop plants to confirm the GRSP roles. Hence, GRSP is one of the most significant multidisciplinary topics between fungal physiology and soil biochemistry. Despite much work performed on glomalin from 1996, there are still gaps of GRSP that needs to be solved, including purification, structural features and environmental responses.